2018
DOI: 10.1080/09297049.2018.1488954
|View full text |Cite
|
Sign up to set email alerts
|

Pitch direction ability predicts melodic perception in autism

Abstract: Individuals with autism spectrum disorders (ASDs) often present atypical auditory perception. Previous work has reported both enhanced low-level pitch discrimination and superior abilities to detect local pitch structure on higher-level melodic tasks in ASD. However, it is unclear how low and high levels of auditory perception are related in ASD or typical development (TD), or how this relationship might change across development and stimulus presentation rates. To these aims, in the present study, children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…Therefore, not all global-to-local paradigms might be adequate to measure holistic perception in terms of Gestalt principles (Wertheimer, 1925). Furthermore, even evidence on a reduced global precedence effect as a result of a more detail-oriented perception in autism is contradictory (Ozonoff et al, 1994; Mottron et al, 1999, 2000, 2003; Foxton et al, 2003; Germain et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, not all global-to-local paradigms might be adequate to measure holistic perception in terms of Gestalt principles (Wertheimer, 1925). Furthermore, even evidence on a reduced global precedence effect as a result of a more detail-oriented perception in autism is contradictory (Ozonoff et al, 1994; Mottron et al, 1999, 2000, 2003; Foxton et al, 2003; Germain et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Again, people with autism spectrum disorders showed a detailed-oriented style in this auditory experiment on cognitive style (Bouvet et al, 2014). However, other authors were not able to replicate a detail-oriented performance of autistic people on hierarchical stimuli (e.g., Mottron et al, 1999, 2003; Foxton et al, 2003; Germain et al, 2018). It is currently under debate if this is caused by variations in experimental setup, variations among autistic people or failure of the theory.…”
Section: Introductionmentioning
confidence: 91%
“…Forms of music therapy have been reported to aid people with severe ASD significantly improve in musical skill in different ways, such as short/long melody recall and rhythm reproduction (Boso et al 2007). However, while some results are consistent with this idea of enhanced musical ability in autism, with reports of increased low-level pitch processing (Bonnel et al 2003), enhanced short-and long-term pitch memory (Stanutz et al 2014), and superior musical processing abilities in ASD (Jiang et al 2015; Molnar-Szakacs and Heaton 2012), a few more recent studies have also found normal (Germain et al 2019) or impaired (Sota et al 2018) performance on pitch discrimination and melodic perception in individuals with ASD. This discrepancy may partly be explained by differences in autism severity between the tested samples: those with enhanced musical abilities tend to have language delay or impairments and those with normal musical processing are generally high functioning (Bonnel et al 2010;Heaton et al 2008;Jones et al 2009;Mayer et al 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Casi el 80 % de los estímulos que percibimos son visuales. Los niños con TEA, no suelen presentar problemas en los órganos de la visión o la audición, pero, sin embargo, la forma en la que procesan la información, y la integran con otros sentidos, es diferente (Bhaskaran, Lawrence, Flora & Perumalsamy, 2018;Germain et al, 2018), con lo cual la percepción de la realidad y la respuesta es también diferente. Se fijan en pequeños detalles, que para cualquier otro pueden pasar desapercibidos, gravándolos con total precisión, pero, sin embargo, no procesan adecuadamente la visión espacial del conjunto de un objeto, espacio o situación, lo cual les crea confusión, en ocasiones deben hacer un barrido región por región para poder reconocer y procesar la información que están recibiendo (Lowe, Stevenson, Barense, Cant & Ferber, 2018;Nilsson Jobs et al, 2018).…”
Section: La Percepción Visual En El Niño Con Teaunclassified